THE INFLUENCE OF ASSET TANGIBILITY, PROFITABILITY, AND LIQUIDITY ON LAVERAGE (Case Study of Miscellaneous Industrial Sector Manufacturing Companies Listed on the Indonesia Stock Exchange 2016 - 2018) - Umratul Khairani; Rahmawati Rahmawati; Helmiati Helmiati (STIE Bangkinang Publishing, 2020)
This research was conducted with the aim of examining the effect of asset tangibility, profitability and liquidity on leverage in various industrial sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The population in this study were all various industrial sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018, numer 52 companies. The technique used in sampling is purposive sampling method, the sample in this study was selected as many as 18 companies. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 22.00 for windows. The results showed that asset tangibility, profitability and liquidity had an effect on leverage. Partially liquidity has an influence on leverage.